Patient experience and primary care teams: a cross-sectional survey of French elderly patients - Cédric Rat; Aurélie Gaultier; Maud Jourdain; Jean-François Huon; Morgane Angibaud; Alice Grimal; Emmanuelle Bataille (BMJ Open)
Objective To assess whether patient experience is better for patients followed in a primary care team (PCT) than for patients with traditional follow-up in usual care.Design A cross-sectional survey based on a self-administered questionnaire.Setting Pays de la Loire geographical area (located on the French west coast).Patients and methods Patients over 75 or over 65 years of age with at least one chronic disease were included. A sample of 9900 frail elderly patients was invited to answer a 23-item questionnaire that investigated four dimensions: ‘communication and patient-centred care’, ‘availability and accessibility’, ‘coordination’ and ‘caregiver’. Their answers were then analysed depending on whether they were followed in a mature PCT, in an emerging PCT or in usual care. The associations between follow-up in a PCT and patient experience were tested with generalised estimation equation models with a Poisson link function, adjusted for sex, age, educational level and the place of residence (French department).Results A total of 4078 responses were received. The result of the assessment for the ‘communication and patient-centred care’ dimension was improved for the participants in the PCT group for the following items: ‘Health professionals were concerned about the impact my health had on my everyday life.’ (RR=1.22, 95% CI (1.04; 1.43)), ‘I have received help to better adapt my everyday life to my health.’ (RR=1.25, 95% CI (1.05; 1.50)), ‘I could take part in decisions concerning my health and care.’ (RR=1.19, 95% CI (1.01; 1.42)) and ‘My consent was requested prior to the transmission of the information between health professionals.’ (RR=1.27, 95% CI (1.09; 1.48)). These assessments were not different between the PCT group and usual care group for other dimensions: ‘availability and accessibility’, ‘coordination’ and ‘caregiver’.Conclusion This study suggests an improved patient experience in regard to the communication perspective for patients in the PCT group. However, it remains unclear whether interprofessional collaboration (IPC) improves overall patient experience. Additional research could explore aspects of IPC that influence patient experience, providing insights to enhance strategies for improving PCTs.